Pulse‐dose radiofrequency can reduce chronic pain in trapezio‐metacarpal osteoarthritis: A mini‐invasive therapeutic approach. (20th May 2015) - Masala, Salvatore; Fiori, Roberto; Raguso, Mario; Calabria, Eros; Cuzzolino, Alessandro; Fusco, Armando; Simonetti, Giovanni
Abstract: Aim: To assess the efficiency of pulse‐dose radiofrequency (PDRF) in the management of chronic pain in patients with trapezio‐metacarpal osteoarthritis (OA). Methods: Seventy‐five patients with trapezio‐metacarpal OA were treated with the PDRF between October 2011 and September 2013. A 22‐gauge cannula with a 5‐cm length was introduced with percutaneous access in the lateral region of the affected trapezio‐metacarpal joint. The PDRF procedure was performed with 1200 pulses at 45 V and 20 msec duration, followed by a 480 msec silent phase. The follow‐up visits were performed at 1 month, 3 and 6 months after the PDRF procedure. All patients underwent a second treatment between 7 and 9 months after the first PDRF procedure with a new follow‐up scheme at 1, 3, 6 and 9 months. Results: Mean visual analogue scale (VAS) scores before the procedures was 8.5 ± 1.1. A great reduction in pain intensity was reported at 3 months after the PDRF procedure (mean VAS scores 3.1 ± 0.9, P < 0.05). Pain intensity began to increase back to pre‐procedural values after 4 months (mean VAS scores at 6 months was 7.9 ± 1.3, P < 0.05). After the second PDRF treatment the mean VAS scores decreased to 3.3 ± 0.8 at 3 months, but increased to 8.1 ± 1.6 at 9 months. ( P < 0.05). No complications after the procedures were observed. Conclusions: The PDRF may be a safe, repeatable and effective short‐term pain management technique in patients with trapezio‐metacarpal OA. Larger, randomized controlled studies are indicated to better clarify the efficacy and utility of the PDRF.